The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/lre.12090
|View full text |Cite
|
Sign up to set email alerts
|

Stratification and water quality of an abandoned opencast coal pit lake at Raniganj Coalfield Area, West Bengal, India

Abstract: Stratification and assessment of the limnological conditions of an abandoned opencast coal pit (OCP), locally called Khadan, which is a potential water reserve located at the Raniganj-Asansol Coalfield Areas of Burdwan, are the main objectives of this study. Water quality changes occurred with increasing depths in the OCP water and suggest a gradual and significant ecological restoration over time, which can create a condition of sustainable pisciculture. The physical and chemical variables of the OCP water ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is known that, according to Mondal et al, (2015), the stratification of the water column due to temperature variation is a seasonal phenomenon in lakes and reservoirs. The study by Grande et al, (2015), on stratification of Metallic and Sulfate Loads, carried out in Dams in the Iberian Pyritic Belt in southwestern Spain, showed that Fe and Mn concentrations increase in the deeper reservoir layer.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…It is known that, according to Mondal et al, (2015), the stratification of the water column due to temperature variation is a seasonal phenomenon in lakes and reservoirs. The study by Grande et al, (2015), on stratification of Metallic and Sulfate Loads, carried out in Dams in the Iberian Pyritic Belt in southwestern Spain, showed that Fe and Mn concentrations increase in the deeper reservoir layer.…”
Section: Analysis Of Variancementioning
confidence: 99%